ADM Scaffolds Generate a Pro-regenerative Microenvironment During Full-Thickness Cutaneous Wound Healing Through M2 Macrophage Polarization via Lamtor1 - He, Chengmin; Yang, Zhi; Jin, Ying; Qi, Xiaoyang; Chu, Jin; Deng, Xiaoyuan (Frontiers in Physiology, 2018)
Adult mammalian skin has a defective regenerative capacity following full-thickness cutaneous injury; this defect overshadows the complete physiological functions of the skin. Immune-mediated skin reconstruction driven by biological scaffolds is a recently developed innovative repair strategy to support regenerative wound healing. However, to date, little is known about how biological scaffolds orchestrate the immune response to promote regeneration. Here, using acellular dermal matrix (ADM) scaffolds, we discovered that the default pro-inflammatory response was altered in response to a pro-regenerative response characterized by specific M2 polarization. M2 macrophages subsequently produced a series of wound healing factors, including matrix metalloproteinases (Mmps) and growth factors which promoted cell proliferation, stabilized angiogenesis and remodeled the extracellular matrix. Our investigations further revealed that the M2 polarization of macrophages arose from an ADM scaffold-derived amino acid sufficiency signal by collagen degradation via macrophage phagocytosis, which activated the acid-sensing pathway (v-ATPase, Lamtor1 and mTORC1). Lamtor1, the acid-sensing pathway-associated lysosomal adaptor protein was critical for inducing M2 polarization, while with the presence of extracellular interleukin 4 (IL4). Our results suggest that ADM scaffolds generate a pro-regenerative microenvironment during full-thickness cutaneous wound healing through M2 macrophage polarization via Lamtor1.